Chlorogenic acid–arabinose hybrid domains in coffee melanoidins: Evidences from a model system. (15th October 2015) - Moreira, Ana S.P.; Coimbra, Manuel A.; Nunes, Fernando M.; Passos, Cláudia P.; Santos, Sónia A.O.; Silvestre, Armando J.D.; Silva, André M.N.; Rangel, Maria; Domingues, M. Rosário M.
Highlights: Melanoidins are formed during coffee roasting. Arabinose was hypothesized as a binding site for chlorogenic acids in melanoidins. Chlorogenic acid–arabinose hybrids were obtained by dry heating of a model mixture. Two of these hybrid structures were identified in coffee derived samples. These results open new perspectives for their identification in coffee melanoidins. Abstract: Arabinose from arabinogalactan side chains was hypothesized as a possible binding site for chlorogenic acids in coffee melanoidins. To investigate this hypothesis, a mixture of 5- O -caffeoylquinic acid (5-CQA), the most abundant chlorogenic acid in green coffee beans, and (α1 → 5)-l -arabinotriose, structurally related to arabinogalactan side chains, was submitted to dry thermal treatments. The compounds formed during thermal processing were identified by electrospray ionization mass spectrometry (ESI-MS) and characterized by tandem MS (ESI-MS n ). Compounds composed by one or two CQAs covalently linked with pentose (Pent) residues (1–12) were identified, along with compounds bearing a sugar moiety but composed exclusively by the quinic or caffeic acid moiety of CQAs. The presence of isomers was demonstrated by liquid chromatography online coupled to ESI-MS and ESI-MS n . Pent1–2 CQA were identified in coffee samples. These results give evidence for a diversity of chlorogenic acid–arabinose hybrids formed during roasting, opening new perspectives for their identification in melanoidin structures.